2022
DOI: 10.1007/s11082-022-03945-9
|View full text |Cite
|
Sign up to set email alerts
|

Design of 2D photonic crystal biosensor to detect blood components

Abstract: Photonic crystals are periodic structures made of insulators. They are the best option to design biosensors. In this paper, a photonic crystal biosensor containing insulation rods in the air was designed and simulated. This biosensor was used as a photonic crystal circular nano-ring between the internal and external waveguides. At the end of the internal waveguide, a defect exists to create an increase in the coupling distance. This causes the quality factor and resonant wavelength displacement to increase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…An artificial neural network (ANN) is used to optimized BPF, and in [ 16 ], an ANN model is used to find transfer function of the branch line coupler. Additionally, higher frequencies for filters and resonators have been achieved using optical fiber substrates [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An artificial neural network (ANN) is used to optimized BPF, and in [ 16 ], an ANN model is used to find transfer function of the branch line coupler. Additionally, higher frequencies for filters and resonators have been achieved using optical fiber substrates [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include optical filters [2][3][4][5][6], along with tunable ones [7][8][9][10][11][12], lasers [13], light-emitting diodes [14], active cavities [15], including optical field enhanced nonlinear absorption [16], optical sensors [17][18][19], fiber-optic sensors [20], humidity sensors [21], gas sensors [22][23][24][25], and photonic biosensors [26][27][28][29][30][31][32]. In addition, alternative designs to the 1DPhC-based optical filters are represented by the 2DPhC-based ones [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zina et al suggested how 1D PC consisting of cold magnetic plasma and quartz materials according to the Copper mean sequence can be used for the detection of the magnetic field direction by studying the external magnetic field dependent movement of ultra large PBG of the structure [39]. Parandin et al suggested a 2D photonic biosensor made up of circular nano-rings between the waveguides for the detection of various blood components [40,41]. Liu et al demonstrated how a 2D PC based cavity structure can be used as a quality sensor for the detection of ethanol [42].…”
Section: Introductionmentioning
confidence: 99%